Pengembangan Bahan Ajar Sejarah Kebudayaan Islam berbasis Higher Order Thinking Skill di MTS Diniyyah Pasia - Melvarisa, Ranti; Junaidi, Junaidi; Ariza, Hidra (Tapis: Jurnal Penelitian Ilmiah, 2023)
Learning material of Islamic Cultural History (SKI) in class VII MTs Diniyyah Pasia only came from books which were not relevant to students' needs. Therefore, the development of valid, effective and practical SKI based on Higher Order Thinking Skill (HOTS) teaching materials is absolutely necessary. This study aims to develop SKI teaching materials based on higher order thinking skills. The methodology used in this research is research and development. The development technique uses a case based reasoning system. The series of learning activities use a scientific approach that is integrated with the 2013 curriculum. The learning models used are problem-based learning, contextual-based learning, and comprehensive concept understanding. The teaching materials that have been developed have met the validity test requirements with a test score of 96% based on expert/lecturer assessments. This teaching materials module has a practicality test score of 91.4% and is declared very practical. This teaching material module is also declared effective with a correlation value of 0.78 and has an influence of 78% on improving student learning outcomes.